The Evolution of the Construction of the Image of China in the Late Ming Dynasty in Europe - Jingxiang, Wei (Sinología hispánica. China Studies Review, 2026)
During China’s late Ming period, European geographical discoveries and navigational activities led to the arrival of the first European missionaries to the Chinese Empire. Many of them recorded their experiences and observations in China, and their writings contributed to the construction of China’s image in European intellectuals. Among them, one of the first encyclopedic treatises on China was Historia de las Cosas más Notables, Ritos y Costumbres del Gran Reyno de la China, written by the Spanish missionary Juan González de Mendoza in 1585. In addition, the work Relación de la entrada de algunos padres de la Compañía de Jesús en la China y particulares sucessos que tuuieron y de cosas muy notables que vieron en el mismo Reyno of the Spanish Jesuit missionary Diego de Pantoja in 1602, also constitutes an important historical document that contributes to the construction of the image of China in the 16th and 17th centuries in Europe, as well as an important text in the first studies of Spanish sinology. Through the comparison and investigation of these two texts, a preliminary understanding of the process of constructing China’s image in Europe can be obtained.